PHYSICAL CULTURE AND SPORT IN ANTIQUE CHINA, JAPAN AND KOREA - Tiahur, R. S.; Lisovskyi, B. P.; Tkachivska, I. M.; Yatsiv, Ya. M. (Rehabilitation and Recreation, 2021)
A little-known in the native science layer of knowledge about the development of physical culture and sport in the countries of Ancient East – China, Japan, Korea – were investigated. Attention is drawn to the participation of ancient Chinese in different sports competitions connected with rituals, military training, social traditions, health and medicine. The aim of the investigation is to analyze the formation development of sport in China, Japan and Korea. The methods of the research: the study is based on the usage of historical analysis of scientific literature, sources and systematic analysis. The results and discussion of the study: the formation of sport activities in Ancient China was associated with self-defense, thus Chinese fighters mastered the wushu technique that became the basis of training for the military and the gymnastics for health improvement. The system of military training had a great impact on the development of physical education and sport in China: archery, horse riding, fencing, boxing, team games that grew into showcase performances. Scientists’ investigations show that the popular game “cuju” is the ancestor of modern football that acquired special significance in the Chinese society. Also such games as “jiju” (horse polo) and “chuiwan” (golf) were very popular. In Ancient Japan there were defined such kinds of sport as sumo, “kemari” (football), “dakyu” (polo), horseback archery, horse racing, the origin of jiu-jitsu and Japanese judo. The origin of taekwondo, “ssirum” (wrestling) and archery were characteristic of Korea. Koreans played with a ball “chuk-guk” similar to Chinese “cuju” and also they played “gyeokgu” (polo) and “chang-chigi” (modern hockey).